Comparative spatial analysis of enteric fever and leptospirosis in Kelantan, Malaysia using e-notifikasi surveillance database, 2016 – 2022 - Hatta, Hazlienor Mohd (2023)
Background: Enteric fever and leptospirosis are increasingly important bacterial causes of acute undifferentiated febrile illness associated with severe complications and higher fatality. The burden of these diseases is high in Northern Malaysia, particularly Kelantan State. Accurate diagnosis is challenging without laboratory confirmation, and despite various public health strategies implemented, enteric fever and leptospirosis remain endemic in Kelantan. Objective: To provide information on the distribution, magnitude, geographical patterns, and risk areas of enteric fever and leptospirosis in Kelantan, and to explore the spatial relationship between the two diseases. Methodology: Laboratory-confirmed enteric fever and leptospirosis cases registered in Kelantan between the years 2016 and 2022 were extracted from the national e-Notifikasi passive surveillance online database. Descriptive and spatial analyses were carried out including incidence and disease mapping, univariate and multitype point pattern analysis, spatial autocorrelation as well as spatial risk variation using spatstat, spdep, sparr, spatialEco and ggplot2 R packages inside RStudio IDE. Result: A total of 212 confirmed cases of enteric fever and 1106 cases of leptospirosis were examined in this study. The average annual incidence for the period of 2016-2022 was 0.016 per 1000 population (95% CI: 0.011, 0.022) for enteric fever and 0.084 per 1000 population (95% CI: 0.071, 0.097). Enteric fever cases were found to be significantly younger than leptospirosis cases, but there was no significant gender difference observed. The study identified seven cases of co-infection, primarily occurring in areas where both diseases were endemic. Both diseases did not show any spatial correlation with population density. Substantial geographical variation of enteric fever and leptospirosis was observed across the state. Enteric fever cases were significantly clustered, and hotspots were predominantly concentrated in the northern part of Kelantan. Leptospirosis cases were as intense as enteric fever in the northern region but exhibited higher spatial intensity in the southern part of Kelantan with higher spatial risk for leptospirosis compared to enteric fever. Leptospirosis was positively spatially autocorrelated with high-high clusters mostly observed in southern and southeastern regions. Spatial dependence between enteric fever and leptospirosis cases within two to ten kilometres distance was also demonstrated. Despite gradual declines in the number of cases for both diseases from 2016 to 2021, there were notable surges observed during the post-COVID-19 pandemic era. Conclusion: Understanding local dynamics is crucial as infectious disease transmission is influenced by various factors, leading to geographical variations in infection risk. Spatial analysis revealed distribution patterns, clustering, and hotspot locations for both diseases, indicating common environmental and socio-economic risk factors for both diseases. Diagnostic algorithms, targeted interventions and early warning systems can be implemented based on these findings to improve disease control and prevention strategies.